Narrative Dimensions and European Theatre, from the Early Twentieth Century to the Present - Marchetti, Marta; Peghinelli, Andrea (Status Quaestionis, 2022)
This monographic issue promotes a discussion on the several ways in which the intersection between narrative dimensions and European theatre has become, since the early Twentieth Century to the present time, a particularly fertile arena in which the identity of the European theatre scene is innovated and reinvented. In their articles, contributors have investigated how the culture of the novel - put into practice by people working in theatre through staging, adapting, playwriting, stage reading, training, workshops and so on - affected the definition of new languages to write, live and think the theatre scene. Our interest has been focused on the complexity of some of the most historiographically meaningful turning points (naturalism, epic theatre, postdramatic theatre etc.), as well as on single instances testifying to the intrinsic multiplicity of a phenomenon which is today more and more rooted in European culture. As a matter of fact, if going to the theatre to ‘watch’ a novel has become an increasingly frequent experience (adaptations, re-writings, appropriations), it is just as easy to find, within new theatre practices, forms and aspects of authoriality indebted to the novel.